Using Process Evaluation Results to Compare Peer and Adult Leader Delivery of the PAWS (Peer-Education about Weight Steadiness) Club Program - Muzaffar, Henna; Nickols-Richardson, Sharon M. (Nutrients, 2021)
To date, there is limited published literature on process evaluation of adolescent health promotion programs. In this paper, we describe the methods and results of PAWS Club process evaluation over 2 years of implementation to compare the effectiveness of delivery by peer and adult leaders. PAWS (Peer-education About Weight Steadiness) Club was a 12-week healthy lifestyle program, delivered to 6th and 7th graders by peer and adult educators, using cluster randomized controlled design. Peer educators were 8th graders in the program schools and adult educators were staff/teachers in the program schools. Trained university students filled out fidelity logs at each session led by peer and adult educators to assess program delivery. The fidelity logs included questions to collect information about the number of participants, duration of the session, percent of activities completed, and if lessons started on time, lesson objectives were clearly stated, lesson objectives were emphasized, demonstrations were visible to participants, all activities were completed, the leader was familiar with lessons, the leader maintained an appropriate pace, the leader kept participants on track, and the leader asked if participants had any questions. Adult educators had a higher mean performance for all questions compared to peer leaders. Significant differences were observed for emphasizing lesson objectives (p = 0.005), making demonstrations visible to participants (p = 0.031), being familiar with the lesson plan (p = 0.000), maintaining an appropriate pace (p = 0.000), keeping participants on track (p = 0.000), and asking if participants had any questions (p = 0.000). Significance was set at p < 0.05. Findings from the current study have implications for designing and conducting a process evaluation of complex healthy lifestyle programs with adolescents in schools. Additional training of peer educators may be needed to enhance program delivery.